Activation of hypoxia-inducible factor 1α: Posttranscriptional regulation and conformational change by recruitment of the Arnt transcription factor - Kallio, Pekka J. (The National Academy of Sciences of the USA, 1997)
In response to hypoxia the hypoxia-inducible factor-1 (HIF-1) mediates transcriptional activation of a network of genes encoding erythropoietin, vascular endothelial growth factor, and several glycolytic enzymes. HIF-1 consists of a heterodimer of two basic helix–loop–helix PAS (Per/Arnt/Sim) proteins, HIF-1α and Arnt. HIF-1α and Arnt mRNAs are constitutively expressed and were not altered upon exposure of HeLa or HepG2 cells to hypoxia, suggesting that the activity of the HIF-1α–Arnt complex may be regulated by some as yet unknown posttranscriptional mechanism. In support of this model, we demonstrate here that Arnt protein levels were not increased under conditions that induce an hypoxic response in HeLa and HepG2 cells. However, under identical conditions, HIF-1α protein levels were rapidly and dramatically up-regulated, as assessed by immunoblot analysis. In addition, HIF-1α acquired a new conformational state upon dimerization with Arnt, rendering HIF-1α more resistant to proteolytic digestion in vitro. Dimerization as such was not sufficient to elicit the conformational change in HIF-1α, since truncated forms of Arnt that are capable of dimerizing with HIF-1α did not induce this effect. Moreover, the high affinity DNA binding form of the HIF-1α–Arnt complex was only generated by forms of Arnt capable of eliciting the allosteric change in conformation. In conclusion, the combination of enhanced protein levels and allosteric change by dimerization defines a novel mechanism for modulation of transcription factor activity.